Identifying key digital prepress competence requirements for printing technology workforce / Muhammad Yusuf Masod … [et al.] - Masod, Muhammad Yusuf; Abdullah, Hamidin; Ahmad, Ridzuan; Shafia, Jumaddi (Research Management Institute (RMI), 2012)
Printing is an industrial process for mass production of texts and images, typically with ink on paper using a press. It is an essential part of publishing, which is defined by Webster as the business or profession of the commercial production and issuance of literature, information, musical scores or sometimes recording or arts. It however does not cover printing or producing of a family history bound book form without commercial intent. Current literature in the field acknowledge that the printing industry is no longer the dominant sector as it is on its way to becoming a multimedia industry. However it will nevertheless remain an important component in the long term. The publishing industry is going through a major transformation which leads to decentralized production, print on demand, and diversified printed products, as well as the development of a new print media market, which is establishing its place between the printing industry, desktop publishing, and online media [1]. Recently, the production of printed products has changed from a crafts men trade into industrial production. The use of conventional typesetting machines, repro cameras and films has been replaced by computer technology in virtually all branches of the printing industry. A study by Shin, Meng-Tsung, Tai (2010), showed the rapid development in the area of computer software and hardware has directly led to comprehensive change in the printing industry [2]. To meet these demands, the workforce must adapt to the rapid development within the digital prepress sector.